If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 4) = 8 + n Reorder the terms: 3(4 + n) = 8 + n (4 * 3 + n * 3) = 8 + n (12 + 3n) = 8 + n Solving 12 + 3n = 8 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 12 + 3n + -1n = 8 + n + -1n Combine like terms: 3n + -1n = 2n 12 + 2n = 8 + n + -1n Combine like terms: n + -1n = 0 12 + 2n = 8 + 0 12 + 2n = 8 Add '-12' to each side of the equation. 12 + -12 + 2n = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 2n = 8 + -12 2n = 8 + -12 Combine like terms: 8 + -12 = -4 2n = -4 Divide each side by '2'. n = -2 Simplifying n = -2
| x^3-4x^2-1=0 | | x^3-x^2+x-6=0 | | 4x+-7=3+2x | | 190-2x=34x+18 | | 4x+-7= | | x^3+2x^2-x+1=0 | | -7(3+4x)= | | 10+6x=-x+10 | | 2x+37=6x-7 | | 2x+1=-4 | | 2x+5=5x-16 | | 9p^2r-73pr-70r=0 | | -.75x=-6 | | r+19=27 | | 4a+8b+11a-10b= | | 5x-1-4x=1x+7 | | 3(7x+6y)=6x | | 3+6x=x-7 | | 2(x+3)+4x=6x+6 | | 6y=8+-9+6y | | 23=11+n | | 4x-6(2x+8)= | | n+2.4=-6.5 | | 0.5(2x-2)=5x+4 | | 4x+7y=71 | | x^2=8100 | | 4x-3x-5=x | | 0.04n=7.2 | | 5(-3x-3)=120 | | 79-2x=16x+15 | | ln*(x-22)=39 | | -2(4y+6)= |